1998
DOI: 10.1037/0022-3514.75.6.1424
|View full text |Cite
|
Sign up to set email alerts
|

The impact of negative affect on autobiographical memory: The role of self-focused attention to moods.

Abstract: Five studies examined how self-focused attention affects the impact of negative moods on autobiographical memory. It was proposed that self-focused attention to moods may increase the likelihood of both mood-congruent recall and mood-incongruent recall and that the type of recall effect that occurs will depend on the manner in which people focus on their moods. In these studies, participants were led to experience negative or neutral moods, exposed to a manipulation designed to affect some aspect of their atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 85 publications
(138 reference statements)
11
120
2
2
Order By: Relevance
“…Nolen-Hoeksema and colleagues suggest that rumination enhances spreading of activation by focusing attention on negative mood and thought content and thereby augmenting and prolonging the affect (Lyubomirsky & Nolen-Hoeksema, 1995, p. 186;Lyubomirsky, Tucker, Caldwell & Berg, 1999). This is supported by a study where it was found that rumination enhanced the mood congruence effect compared to reflection (McFarland & Buehler, 1998). Also studies show that participants who ruminate while in a negative mood recall more negative memories compared to individuals who distract, suggesting that rumination enhances the spread of activation between the affect node and the related memories (e.g., Rusting & Nolen-Hoeksema, 1998).…”
Section: Maladaptive Repetitive Thinking and Mental Time Travelsupporting
confidence: 75%
“…Nolen-Hoeksema and colleagues suggest that rumination enhances spreading of activation by focusing attention on negative mood and thought content and thereby augmenting and prolonging the affect (Lyubomirsky & Nolen-Hoeksema, 1995, p. 186;Lyubomirsky, Tucker, Caldwell & Berg, 1999). This is supported by a study where it was found that rumination enhanced the mood congruence effect compared to reflection (McFarland & Buehler, 1998). Also studies show that participants who ruminate while in a negative mood recall more negative memories compared to individuals who distract, suggesting that rumination enhances the spread of activation between the affect node and the related memories (e.g., Rusting & Nolen-Hoeksema, 1998).…”
Section: Maladaptive Repetitive Thinking and Mental Time Travelsupporting
confidence: 75%
“…This possibility is supported by evidence that rumination is only one of a number of possible modes of self-focus, each of which has distinct functional properties (McFarland and Buehler, 1998;Trapnell and Campbell, 1999;Watkins and Teasdale, 2001).…”
Section: Introductionmentioning
confidence: 48%
“…In investigations of community-dwelling adults, ruminative style has been found to be associated with a pessimistic outlook (Nolen-Hoeksema et al, 1994) and a reduced sense of mastery over one's life Nolen-Hoeksema & Jackson, in press; see also Waenke & Schmid, 1996). Corroborating the results from the rumination induction studies, individuals with a tendency to ruminate have also been found to express negativelybiased thoughts in free associations, to evaluate both themselves (Ward, Lyubomirsky, Sousa, & Nolen-Hoeksema, 2002) and their families (Aymanns, Filipp, & Klauer, 1995) in an unfavorable way, to recall negatively-biased memories (McFarland & Buehler, 1998, Studies 3, 4, and 5), and to show low self-confidence in their plans (Ward et al, 2002).…”
Section: Negatively-biased Thinkingmentioning
confidence: 99%